Friday

December 19, 2014

December 19, 2014

Posted by **Ashley** on Tuesday, December 27, 2011 at 9:13pm.

- arithmetic -
**Reiny**, Tuesday, December 27, 2011 at 10:51pmSo Sum(5) - Sum(4) = term(5)

85-(-8) = a + 4d

a+4d = 93 < (#1)

Sum(4) = -8 , since there are only 4 terms I will not use the sum formula

a + a+d + a+2d + a+3d = -8

4a + 6d = -8

2a + 3d = -4 , (#2)

2(#1) - (#2) ---> 5d = 190

d = 38

in #1, a = -59

check:

-59 - 21 + 17+ 55 = -8

sum(5) = sum(4) + term(5) = -8 + (-59+4(38)) = 85

**Answer this Question**

**Related Questions**

arithmetic - In an arithmetic series, the terms of the series are equally spread...

Algebra - In an arithmetic series, the terms of the series are equally spread ...

sequences and series - how do i solve the sum of the first two terms of an ...

math sequences and series - how do i solve the sum of the first two terms of an ...

maths - 1) The first term of arithmetic progression is -20 and the sum of it's ...

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

Math(arithmetic & Geometric Series) - 1)The sum of 6 terms of an arithmetic ...

math - The sum of the first 20 terms of an arithmetic series is identical to the...

Math - the sum of the first n terms of an arithmetic series is -51. the series ...

math - The sum of the first 10 terms of an arithmetic series is 145 and the sum ...